The Role of Metaverse Technology in Education: A Systematic Review of Opportunities, Challenges, and Educational Potential - Zümrüt Varol Selçuk; Gamze Mercan (Sakarya University Journal of Education)
This study investigates the application of the metaverse in educational settings, focusing on its development, implementation, and impact on learning outcomes. Employing a systematic literature review methodology, the research meticulously followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure a comprehensive and unbiased collection of data. Searches were conducted on major databases including Web of Science and Scopus, covering literature from January 2007 to June 2023. Consequently, a comprehensive bibliometric review was executed, harnessing the repositories of Web of Science (WoS) and Scopus. In pursuit of a comprehensive educational objective, the approach eschewed the imposition of restrictions pertaining to time frames, pedagogical stratification, or subject-specific criteria. Given the novelty of the metaverse topic and considering the inclusionary and exclusionary parameters, a compilation of 17 scholarly pieces was critically evaluated. The results elucidate the metaverse's intrinsic capacity to augment and revolutionize pedagogy, fostering elevated educational yields and bolstering student involvement and enthusiasm. The study categorizes the primary aims of metaverse applications in education, which include the development of virtual worlds, creation of specific educational tools such as avatars and virtual labs, and pedagogical innovations tailored for immersive environments. Key findings suggest that the educational metaverse fosters significant improvements in student engagement and collaboration, enhances digital proficiency, and supports diverse pedagogical approaches. Despite these advantages, challenges related to technological integration, accessibility, and the scalability of findings due to small sample sizes were identified. The study underscores the need for future research to expand on methodological diversity and larger participant groups to validate and generalize the results across different educational contexts. This research contributes to the academic discourse by providing a detailed overview of the current state of metaverse utilization in education, highlighting both its potential and limitations. The findings aim to guide future studies and inform educational practices and policy-making in integrating virtual reality technologies.